Trade-offs between burrowing and biting force in fossorial scincid lizards?. (18th May 2020) - Le Guilloux, Margot; Miralles, Aurélien; Measey, John; Vanhooydonck, Bieke; O'Reilly, James C; Lowie, Aurélien; Herrel, Anthony
Abstract: Trade-offs are thought to be important in constraining evolutionary divergence as they may limit phenotypic diversification. The cranial system plays a vital role in many functions including defensive, territorial, predatory and feeding behaviours in addition to housing the brain and sensory systems. Consequently, the morphology of the cranial system is affected by a combination of selective pressures that may induce functional trade-offs. Limbless, head-first burrowers are thought to be constrained in their cranial morphology as narrow heads may provide a functional advantage for burrowing. However, having a wide and large head is likely beneficial in terms of bite performance. We used 15 skink species to test for the existence of trade-offs between maximal push and bite forces, and explored the patterns of covariation between external head and body morphology and performance. Our data show that there is no evidence of a trade-off between bite and burrowing in terms of maximal force. Species that generate high push forces also generate high bite forces. Our data also show that overall head size covaries with both performance traits. However, future studies exploring trade-offs between force and speed or the energetic cost of burrowing may reveal other trade-offs.